Strategi Manajemen Islami Untuk Keberlanjutan BMT Di Era Digital: Studi Literatur - Akmal Syawqi Albar; Dedy Rachmad; Aslichan (Institut Muslim Cendekia, 2025)
Baitul Maal wa Tamwil (BMT) is pivotal to Islamic financial inclusion and MSME resilience; however, digital disruption, financing risks, and governance gaps challenge its sustainability. A clear sustainability strategy is crucial for BMT's competitiveness and its contribution to the national Islamic finance agenda. This study formulates an integrated Islamic management framework to strengthen BMT sustainability in the digital era. An integrative literature review (2021–2025) with thematic synthesis was employed. Sources include peer-reviewed national/international journals, as well as pertinent regulations. Studies were identified through keyword searches (